Considerations for standardizing fluid station practices among road races - Cheuvront, S. N.; Sollanek, K. J. (Strength and Conditioning Journal, 2020)
Road race event planners have the paramount task of providing runners with appropriate access to fluid along race courses. Important variables for consideration include weather conditions, participant numbers, and racing distances. In an effort to standardize practices among road races, this review describes novel improvements to the traditional approach for estimating total fluid needs and fluid station numbers. Recommendations for fluid station numbers and positioning are given to serve as a starting point for standardizing fluid station practices among road races.